Day Care for School-Age Children. Final Report - Unco, Inc., Washington, DC.; Unco, Inc., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This report provides some perspectives on existing school-age child care and proposes some alternative school-age care program models which maximize the use of community resources and, thus, reduce potentially high costs. Chapters One and Two examine the current school-age "child care" services both nationally and in Region X (Oregon, Washington State, Idaho, and Alaska). Chapter Three briefly explores parent expectations for school-age child care programs as expressed in interviews with parents conducted during a larger study of Region X child care services. Chapter Four presents some of the important planning considerations in developing school-age care programs, while Chapter Five sets out several general models for school-age care programs which combine the most successful features of existing programs with various other cost-saving features. These recommended models for school-age care programs are: (1) Recreation and Leisure Time Program Coordination Model, (2) Community School Based Model, (3) Family Day Care Services Coordination Model, (4) Family Day Care Home/Neighborhood Parks Model for Full Day Summer School-Age Care, and (5) Residential Cluster Model with "Cultural Enrichment" Cmponents. A description of the advantages and disadvantages of each model is discussed, along with an ouline of the model assumptions, approprite groups served by the model, staff requirements, major cost factors, and potential funding sources. Descriptions of operating programs are included. (CS)
Sponsoring Agency: Department of Health, Education, and Welfare, Washington, DC.
Contract Number: OEC-X-72-0055.
ERIC Note: For related documents see PS 007 808 through PS 007 811.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Care; Child Caregivers; Community Resources; Cost Effectiveness; Day Care; Educational Planning; Elementary School Students; Family Day Care; Financial Support; Models; National Surveys; Nontraditional Education; Parent Participation; Program Development; Program Evaluation; Staff Role; State Surveys; Reports, Research